Arteriovenous Fistula—A Rare Complication of IVC Filter Retrieval. (August 2019) - DeSai, Charisma; Lamus, Daniel; Kumar, Girish
Inferior vena cava (IVC) filters are important devices for patients who are at high risk for developing thrombi and pulmonary embolism but have conditions that preclude the use of pharmacologic anticoagulants. IVC filter retrieval has become an important quality initiative backed by Food and Drug Administration guidelines for prompt removal after the filter is no longer indicated. Filter retrieval is a common procedure that usually has very few complications. However, when the filter is tilted or embedded in the caval wall, advanced techniques of retrieval may be necessary. These techniques have a higher rate of success but also a higher risk of complications such as injury to the IVC. Here, we describe a case of IVC filter retrieval resulting in formation of an arteriovenous fistula between the right renal artery and IVC and subsequent successful repair of this fistula using a vascular plug.